SIMULATION OF THE OPERATOR WORKING CAPACITY OF UNMANNED AIRCRAFT COMPLEXES BASED ON CARDIAC RHYTHM - A. G. Davidovsky; A. I. Andreev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The number of parameters of the cardiac rhythm to analyze the health of operators of unmanned aircraft systems has been presented. Three mathematical models of the dynamics of health and functional operators activity made on the basis of parameters of cardiac rhythm were proposed.